The Effect of Progressive Tax on Regional Income: Study at One of The Centers of Income Management in Cimahi City - Deswita Maharani; Mochamad Kohar Mudzakar (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
This study aims to explore the effect of Progressive Tax on Regional Original Income, one of the SAMSAT Revenue Management Centers in Cimahi City, for 2018-2022. Progressive Tax is an independent variable, while Local Own Revenue is the dependent variable. This research method uses quantitative research methods with a descriptive approach. The results of this study indicate that Progressive Taxes have a significant effect on Regional Original Income. To increase the effect of Progressive Tax on Regional Original Income, one of the SAMSAT Revenue Management Centers in Cimahi City. It is best to strengthen related laws and regulations and improve the performance of regional apparatus to optimize tax revenue and original regional income.